The Role of a P1-Type ATPase from Pseudomonas fluorescens SBW25 in Copper Homeostasis and Plant Colonization - Xue-Xian Zhang; Paul B. Rainey (Molecular Plant-Microbe Interactions, 2007)
The genome of the plant-colonizing bacterium Pseudomonas fluorescens SBW25 possesses a putative copper-transporting P1-type ATPase (CueA) that is induced on the plant surfaces. Using a chromosomally-integrated cueA-'lacZ fusion, we show that transcription of cueA can be induced (in vitro) by ions of copper, silver, gold, and mercury. To investigate the biological significance of cueA, a nonpolar cueA deletion mutant (SBW25ΔcueA) was constructed. This mutant strain displayed a twofold reduction in its tolerance to copper compared with the wild-type strain; however, no change was observed in the sensitivity of the mutant strain to silver, gold, or mercury ions. To obtain insight into the ecological significance of cueA, the competitive ability of SBW25ΔcueA was determined relative to wild-type SBW25 in three environments (none contained added copper): minimal M9 medium, the root of sugar beet (Beta vulgaris), and the root of pea (Pisum sativum). Results showed that the fitness of SBW25ΔcueA was not different from the wild type in laboratory medium but was compromised in the two plant environments. Taken together, these data demonstrate a functional role for CueA in copper homeostasis and reveal an ecologically significant contribution to bacterial fitness in the plant rhizosphere. They also suggest that copper ions accumulate on plant surfaces.